2009
DOI: 10.1016/j.sedgeo.2008.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Are beds in shelf carbonates millennial-scale cycles? An example from the mid-Carboniferous of northern England…

Abstract: The mid-Carboniferous strata of northern England are characterised by mixed clastic-carbonate cycles (Yoredale cyclothems), attributed here to the short eccentricity Milankovitch rhythm. In a typical cycle, transgressive normal-marine shelf carbonates are succeeded by marine shales, then highstand prodelta mudstones and delta front-delta top sandstones with local coals. A detailed study of one cycle, the Great Limestone Cyclothem of the northern Pennines (Alston Block), reveals that within the transgressive ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…For example, high-frequency sequences controlled by orbital forcing may develop at scales comparable to, or even smaller than, those of many parasequences (e. g., Strasser et al 1999;Fielding et al 2008;Tucker et al 2009). As such, even cycles as thin as a meter can sometimes be referred to as sequences and be described and interpreted in terms of sequence stratigraphic surfaces and systems tracts (e. g., Posamentier et al 1992a;Strasser et al 1999;Tucker et al 2009). We recommend the use of the sequence stratigraphic methodology to the analysis of any small, meter-scale cycles, as long as they display depositional trends that afford the recognition of systems tracts and diagnostic bounding surfaces.…”
Section: Scale and Stacking Patternsmentioning
confidence: 99%
“…For example, high-frequency sequences controlled by orbital forcing may develop at scales comparable to, or even smaller than, those of many parasequences (e. g., Strasser et al 1999;Fielding et al 2008;Tucker et al 2009). As such, even cycles as thin as a meter can sometimes be referred to as sequences and be described and interpreted in terms of sequence stratigraphic surfaces and systems tracts (e. g., Posamentier et al 1992a;Strasser et al 1999;Tucker et al 2009). We recommend the use of the sequence stratigraphic methodology to the analysis of any small, meter-scale cycles, as long as they display depositional trends that afford the recognition of systems tracts and diagnostic bounding surfaces.…”
Section: Scale and Stacking Patternsmentioning
confidence: 99%
“…() identified high‐frequency cyclicity producing shallowing‐upward sequences in the Triassic Latemar platform, and Tucker et al . () explained mid‐Carboniferous cyclothems by high‐frequency arid‐humid climate changes that were superimposed on climate and sea‐level changes induced by the orbital precession cycle. These high‐frequency climate changes were possibly controlled by variations in solar activity (Elrick & Hinnov, ).…”
Section: Discussionmentioning
confidence: 99%
“…Not only orbitally induced processes in the Milankovitch frequency band but also millennial-scale cyclical processes may create laterally consistent bedding planes. For example, Z€ uhlke et al (2003) identified highfrequency cyclicity producing shallowing-upward sequences in the Triassic Latemar platform, and Tucker et al (2009) explained mid-Carboniferous cyclothems by high-frequency arid-humid climate changes that were superimposed on climate and sea-level changes induced by the orbital precession cycle. These high-frequency climate changes were possibly controlled by variations in solar activity (Elrick & Hinnov, 2007).…”
Section: From the Living Platform To The Depositional Recordmentioning
confidence: 99%
“…One of these beds would thus represent 3-4 kyr. Allocycles with shorter frequencies than those of the orbital cycles have been identified for example in the Triassic Latemar platform (Zühlke 2004) or in the Carboniferous of England (Tucker et al 2009). However, these then should leave a platform-wide imprint, which is not the case in the studied Berriasian sections.…”
Section: Facies Evolution Through Space and Timementioning
confidence: 95%
“…Clays can be washed onto the platform when rainfall increases in the hinterland, when relative sea level drops and forces erosion of soils and progradation of deltas, or when sea level rises and remobilizes clays from flooded coastal areas (Tucker et al 2009). Also, clays can be ponded in lagoons if water energy decreases.…”
Section: Small-scale Sequence 13mentioning
confidence: 99%